Self built of laboratory scale supercritical anti solvent system - Chong, G. H.; R., Yunus; Choong, Thomas Shean Yaw; Abdullah, N.; Spotar, S. Y. (2010)
Supercritical fluid (SCF) particles formation technique gained a significant attention mainly in the pharmaceutical, cosmetic and paints. However, the scarcity of information on the design and process for this type of laboratory scale equipment is a significant drawback to the technological progress. Therefore, the purpose of this study was to design and build a laboratory supercritical anti solvent (SAS) system for producing microparticles and microcapsules of acetaminophen. The operating conditions of the constructed system affected the yield. The optimum operating conditions were then determined as: 110 bars, 35° C, 35 mg/ml of polymer concentration and 1.75 ml/min of feed flow rate. The microparticles and microcapsules were characterized on its morphology (scanning electron microscopy), size distribution (particle size analyzer), thermal properties (thermo gravimetetric analyzer) and crystallographic (X-ray powder diffraction). The in vitro drug released of the microparticles and microcapsules were also investigated. The results revealed a more homogenous microparticle size distribution, a change in the crystalinity and maintained of drug thermal stability after the SAS process. Furthermore, the microcapsules prolong the drug released significantly in the in vitro study.